Recommended first-line management of brain metastases from melanoma: A multicenter survey of clinical practice. (March 2022) - Jablonska, Paola Anna; Fong, Chin Heng; Kruser, Timothy; Weiss, Jessica; Liu, Zhihui Amy; Takami, Hirokazu; Narita, Yoshitaka; Ynoe de Moraes, Fabio; Dasgupta, Archya; Ong, Choo Khoon; Yang, James C.H.; Lee, Jih Hsiang; et al.
Highlights: International survey of treatment recommendations from melanoma brain metastasis (MBM) experts. MBM management recommendations varied significantly according to specialty. Multidisciplinary approach is critical for appropriate individual treatment. Abstract: Background: Radiotherapy (RT) and surgery (Sx) are effective in treating brain metastases. However, immune checkpoint inhibitors (ICI) have shown activity against asymptomatic melanoma brain metastases (MBM). BRAF/MEK inhibitors can be used to treat BRAF V600 mutation positive (BRAF+) MBM. Method: We conducted an international survey among experts from medical oncology (MO), clinical oncology (CO), radiation oncology (RO), and neurosurgery (NS) about treatment recommendations for patients with asymptomatic BRAF+ or BRAF mutation negative (BRAF−) MBM. Eighteen specific clinical scenarios were presented and a total of 267 responses were collected. Answers were grouped and compared using Fisher's exact test. Results: In most MBM scenarios, survey respondents, regardless of specialty, favored RT in addition to systemic therapy. However, for patients with BRAF+ MBM, MO and CO were significantly more likely than RO and NS to recommend BRAF/MEK inhibitors alone, without the addition of RT, including the majority of MO (51%) for patients with 1–3 MBM, all <2 cm. Likewise, for BRAF− MBM, MO and CO more commonly recommended single or dual agent ICI only and dual agent ICI therapy alone was the most common recommendation from MO or CO for MBM <2 cm. When at least 1 of 3 MBM (BRAF+ or BRAF−) was >2 cm, upfront Sx was recommended by all groups with the exception that MO and RO recommended RT for BRAF− MBM. Conclusions: In most clinical settings involving asymptomatic MBM, experts recommended RT in addition to systemic therapy. However, recommendations varied significantly according to specialty, with MO and CO more commonly recommending dual systemic therapy alone for up to 9 BRAF− MBM <2 cm.